Mechanisms and effects of metformin on skeletal muscle disorders - Shang, Ren; Miao, Jing (Frontiers in Neurology, 2023)
Skeletal muscle disorders are mostly genetic and include several rare diseases. With disease progression, muscle fibrosis and adiposis occur, resulting in limited mobility. The long course of these diseases combined with limited treatment options affect patients both psychologically and economically, hence the development of novel treatments for neuromuscular diseases is crucial to obtain a better quality of life. As a widely used hypoglycemic drug in clinical practice, metformin not only has anti-inflammatory, autophagy-regulating, and mitochondrial biogenesis-regulating effects, but it has also been reported to improve the symptoms of neuromuscular diseases, delay hypokinesia, and regulate skeletal muscle mass. However, metformin’s specific mechanism of action in neuromuscular diseases requires further elucidation. This review summarizes the evidence showing that metformin can regulate inflammation, autophagy, and mitochondrial biogenesis through different pathways, and further explores its mechanism of action in Duchenne muscular dystrophy, statin-associated muscle disorders, and age-related sarcopenia. This review clarifies the directions of future research on therapy for neuromuscular diseases.